Cell-Seeded Extracellular Matrices for Bladder Reconstruction: An ex vivo Comparative Study of their Biomechanical Properties. Issue 4 (April 2013) - Davis, Niall F.; Mooney, Rory; Piterina, Anna V.; Callanan, Anthony; Flood, Hugh D.; McGloughlin, Tim M.
Purpose: Autogenous ileal tissue remains the gold-standard biomaterial for bladder replacement purposes; however, cell-seeded extracellular matrix (ECM) scaffolds have shown promise. Although the biological advantages of cell-seeded ECMs in urological settings are well documented, there is a paucity of data available on their biomechanical properties. In this study, the biomechanical properties of cell-seeded ECMs are compared with autogenous ileal tissue. Methods: Human urothelial cells (UCs) and smooth muscle cells (SMCs) were obtained by bladder biopsy and cultured onto porcine urinary bladder matrix (UBM) scaffolds under dynamic and static growth conditions for 14 days. The biomechanical properties of cell-seeded UBM (n = 12), and porcine ileum (n = 12) were determined with uni-axial tensile testing protocols and compared with stress-strain curves. In addition, their biomechanical properties were compared with porcine bladder tissue (n = 12) and unseeded UBM (n = 12). Results: There were significant differences in the biomechanical properties of each biomaterial assessed. Strain to failure occurred at 92 ± 24% for dynamically cultured cell-seeded UBM compared to 42.2 ± 5.20% for ileal tissue (p<0.01). Values for linear stiffness at 30% strain were significantly lower in dynamically cultured cell-seeded UBM compared to ileal tissue (0.36 ± 0.14 MPa versus 0.67 ± 0.32 MPa respectively, p<0.01). Bladder tissue remained the most distensible biomaterial throughout, with linear stiffness measuring 0.066 ± 0.034 MPa at 30% strain. Conclusions: Dynamically cultured cell-seeded ECMs are biomechanically superior to ileal tissue for bladder replacement purposes. Additional comparative in vivo studies will be necessary before their role as a reliable alternative is clearly established.